MISCONCEPTION REMEDIATION THROUGH ANALOGY TO INCREASE THE UNDERSTANDING OF LEARNERS CONCEPTS IN ROTATIONAL DYNAMICS SUBJECT - Novita Sari, Dian; Linuwih, Suharto; Sulhadi, Sulhadi (Physics Communication, 2019)
This research aims to a11alyze the basic concepts that form a pattern of misconceptions on the rotational dyna111ics. The misconceptions formed by several incorrect patterns of concepts are remediated using a11alogy leaming method. This research is applied using the mix method (qualitative and quantitative). Quantitative data is taken using two tier diagnostic tests for pretest and posttest which consists of 10 questions. Qualitative data is taken by applying direct observations and interviews with the students. The result of the pretest showed a misconception average of 83.8%. Analogy learning process with posttest. After leaming analogy done, the result of posttest showed that misconceptions average decreased to 41.9%. With the decreasing in the posttest, the understanding of concepts average has increased from 16,2 % to 53,6 %. However, the results of this study cannot be said to be effective because there is still incorrect concept pattern from the posttest results. This is due to interest of student in physics, the student ability and the cognitive development.